Global Capital and Local Assets: House Prices, Quantities, and Elasticities - Gorback, Caitlin S; Keys, Benjamin J (Review of Financial Studies, 2026)
Abstract We estimate price elasticities of housing supply for U.S. cities by examining the impact of foreign purchases on housing prices and quantities. After other countries introduced foreign-buyer taxes beginning in 2011, both house prices and quantities increased more in locations with high foreign-born populations. An increase in global capital inflows, instrumented with tax policy changes scaled by immigrant exposure, increased prices and quantities over 2011–2018. We combine these estimates to construct new local supply elasticities, which average 0.26 and range from 0.06 to 0.9. Compared to prior estimates, our elasticities are more inelastic and change cities’ relative rankings.